Social Presence Online Tutoring: A study of Peer Effect Mechanism - Mudafiatun Isriyah (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study is to analyze whether Social Presence affects students' learning completeness in distance learning? at the University of PGRI Argopuro Jember (N = 600), the assessment was measured by Grade-Point Average (GPA). Data, obtained from variables consisting of: variable composition of students, class environment and the average value of students. Previous research has stated that Social Presence affects positive attitudes that have an impact on student learning mastery. It was found that the effect of learning enthusiasm that affects learning success with a high GPA difference was found. Students with high social presence get a complete average score in all of their competencies. The results show that the effects that influence students on the composition of Social Presence and frame factors are class composition, student interaction, and teacher interaction.